Avaliação das condições de fermentação na produção de off flavors da cerveja - Benatti Monetta, Gabriel (Universidade Federal de São Carlos, 2025)
Beer, one of the most consumed beverages in the world and in Brazil, holds significant economic and social importance for society, as it is consumed during various moments in people's lives. It is produced using four main ingredients: barley (malt), hops, water, and yeast. These four ingredients form the basis for the production process, which is divided into two parts: the hot and cold stages. The hot stage consists of receiving raw materials, processing, and mashing, which is the step of preparing the wort. The cold stage involves fermentation, maturation, filtration, and packaging. The fermentation stage is where the main biochemical reactions of the process occur, and some volatile compounds responsible for the flavor and aroma of the beer are formed. These compounds need to be controlled so that they do not turn into undesirable flavors (known as off-flavors) when present in high concentrations. Therefore, this work focuses on the fermentation stage of the brewing process, with the collection of thirty samples of fermentations containing their pre-established ranges for each operational parameter. The analysis of these data was performed through scatter plots, radar charts, and heatmaps to assess how the operational parameters influence the formation of these substances, using the Microsoft Excel® software. As a result of this work, it was possible to observe how some operational parameters, such as temperature and aeration, impact the elevated formation of acetaldehyde, and that fine-tuning the pre-established process conditions is a way to control the formation of volatile compounds, resulting in a more harmonized beer without them reaching high concentrations and becoming offflavors.
Assessment of fermentation conditions affecting off-flavor formation in beer
Keywords: Cerveja; Fermentação; Bioquímica; Compostos voláteis; Aroma; Sabor; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA